Saturnino de Brito and Sanitary Layout of the city of Santa Maria/RS - Piccinato Junior, Dirceu (Risco - Journal of Architecture and Urbanism, 2021)
The purpose of this article is to discuss the sanitary layout of Santa Maria, a city in the state of Rio Grande do Sul, from the perspective of the urban sanitary form articulated by sanitary engineer Saturnino de Brito in 1918. The urbanization process that took place from the first decades of the 20th century was decisive for the growth of Brazilian cities in inadequate socio-environmental conditions. With the advances in microbiology, there appears the figure of a professional who had the domain to act in the face of this reality: the sanitary engineer. Brito's understanding of sanitary urbanism had two themes in mind: health problems in the transformation of urban spaces and the construction of cities.